Neuroimmune Interactions in Inflammation and Acute Kidney Injury - Inoue, Tsuyoshi; Tanaka, Shinji; Okusa, Mark D. (Frontiers in Immunology, 2017)
Inflammation contributes to the pathogenesis of a wide variety of disorders including kidney diseases. Recent advances have shown that neural pathways are able to regulate immunity and inflammation. The cholinergic anti-inflammatory pathway is a well-studied neural circuit involving the vagus nerve that is thought to contribute to the response to inflammatory disorders. Expression of receptors for neurotransmitters are found in some immune cells, including β2 adrenergic receptors on CD4 T cells and alpha 7 subunit of the nicotinic acetylcholine receptor on macrophages. Once nerves are activated, neurotransmitters such as norepinephrine and acetylcholine are released at nerve terminals, and the neurotransmitters can activate immune cells located in close proximity to the nerve terminals. Thus vagus nerve stimulation induces activation of immune cells, leading to an anti-inflammatory response. Recent studies demonstrate a nonpharmacological organ protective effect of electrical nerve stimulation, pulsed ultrasound treatment or optogenetic C1 neuron activation. These modalities are thought to activate the cholinergic anti-inflammatory pathway and attenuate inflammation. In this review, we will focus on the current understanding of the mechanisms regarding neuro-immune interactions with a particular focus on inflammation associated with kidney disease.